Enhancing the Efficacy of Radiation Therapy and Chemotherapy in Cancer Treatment with Modified Citrus Pectin and Metformin - Vityala, Yethindra (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Radiation therapy, a commonly used treatment for various types of cancer, has toxic effects on the body. To counter this, researchers have developed medications that minimize the harmful effects of ionizing radiation on normal cells and tissues, while enhancing the effect of radiation on cancerous cells. These drugs are known to be radiosensitizers or radiomimetic agents. This study investigated the effectiveness of modified citrus pectin (MCP) and metformin combined with radiation therapy and chemotherapy. Materials and Methods: This study used 380 Wistar rats with transplantable strains and two types of cancer cells. The experimental therapy included administration of sugar beet pectin, MCP, and metformin. Effectiveness was determined by commonly accepted indicators, such as the percentage of tumor growth inhibition and increased lifespan. Results: MCP and sugar beet pectin had radiomodifying properties and enhanced the sensitivity of cancer cells to radiation therapy. The combination of MCP and metformin had a positive effect on cancer treatment, with complete regression or disappearance of the tumor by the 15th day, and the lifespan of the animals increased by approximately 430%. Conclusion: The use of pectin and MCP as radiomodifiers could potentially improve the effectiveness and reduce the toxicity of anti-tumor therapy. This study suggests that the combination of MCP and metformin with radiation therapy and chemotherapy may be a promising approach for cancer treatment.